The Role of Mikhail Speransky in the Financial System Reform - LUKOVSKAYA, Dzhenevra; SHEVELEVA, Natalya; VOLKOVA, Svetlana; VASILYEV, Ilya; ILYIN, Andrey (Journal of Advanced Research in Law and Economics; Vol 7 No 6 (2016): Vol 7, No 6(2016): JARLE, Volume VII, Issue 6(20), Fall 2016, 2017)
The article is devoted to the reform of the financial system in Russia (1810 – 1812), prepared by Prime Minister Mikhail Speransky. The reform program included the issuance of credit securities (bank notes), the establishment of a fixed exchange rate of the ruble, and the exchange of assignations on banknotes in accordance with the exchange rate. Assignations issued earlier in treatment, were declared as duty of the state; it was declared the cease further production of assignations and of the decision to pay off the national debt by entering into a domestic loan. As a result, the funding of the state apparatus has reduced. A financial fund was created for the compensation of assignations withdrawn from circulation that have fallen into the category of public debt. Free credit relations between enterprises were allowed. The national monetary system strengthened. The implementation of 1810 – 1812 financial reforms were interrupted by the invasion of Napoleon in Russia, but it marked the shift of attitude of the supreme power in relation to the financial functions of the state. The financial system reform laid the foundation for the modern Russian budgetary system.
Keywords: financial system; budgetary system; Speransky; Russia